2007
DOI: 10.2214/ajr.05.2198
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Diffusion-Weighted MRI and 1H MR Spectroscopy to Increase Accuracy in Prostate Cancer Detection

Abstract: When voxels containing > or = 70% tumor are considered positive, the combined use of MR spectroscopy and diffusion-weighted MRI increases the specificity for prostate cancer detection while retaining the sensitivity compared with MR spectroscopy alone or diffusion-weighted MRI alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
132
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 26 publications
(35 reference statements)
10
132
1
5
Order By: Relevance
“…Chen et al (45) found that DWI (82%) and MRS (84%) had similar sensitivity but DWI had lower specificity (82%) compared with MRS (98%). In contrast, Reinsberg et al (46) instead showed slightly lower sensitivity and specificity rates of DWI compared with that of MRS, particularly when the percentage of tumor within the voxel was smaller.…”
Section: Discussionmentioning
confidence: 88%
“…Chen et al (45) found that DWI (82%) and MRS (84%) had similar sensitivity but DWI had lower specificity (82%) compared with MRS (98%). In contrast, Reinsberg et al (46) instead showed slightly lower sensitivity and specificity rates of DWI compared with that of MRS, particularly when the percentage of tumor within the voxel was smaller.…”
Section: Discussionmentioning
confidence: 88%
“…Chen et al [48] found that DWI (82%) and MRS (84%) had similar sensitivity but DWI had lower specificity (82%) compared with MRS (98%). Reinsberg et al instead showed slightly lower sensitivity and specificity rates of DWI compared with MRS, particularly when the percentage of tumour within the voxel was smaller (see section on voxel size) [50]. Mazaheri et al found that the AUC for DWI was higher (0.81) than for MRS (0.74), but results were better when both techniques were combined (0.85).…”
Section: Mr Spectroscopymentioning
confidence: 99%
“…Reinsberg et al [50] noted that DWI with the tumour occupying approximately 30% of the voxel, sensitivity and specificity were 67% and 60%, but when tumour occupied approximately 70% of the voxel, sensitivity and specificity increased to 93% and 57% respectively. In the recent study by Langer et al [64] it was shown that DWI is unable to differentiate between sparse PC (as defined by tumour of less than 40% within the lesion) and normal PZ tissue.…”
Section: Voxel Sizementioning
confidence: 99%
“…In recent years, the utility of diffusion-weighted imaging (DWI) in the diagnosis of prostate cancer has been reported in a number of preliminary studies, leading to high expectations for clinical applications as an additional method to T2-weighted imaging, dynamic MR studies, and MR spectroscopic imaging (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, all of these studies have focused on comparisons between cancer and normal regions in prostate cancer patients and limited cases of healthy individuals.…”
mentioning
confidence: 99%